A Comprehensive Review on Solid Lipid Nanoparticles - A.Subodh, Urkunde; Sandeep, Atram C.; Rupali, Sable P.; Vrunda, Rajput J.; Anuja, Gawai G. (Asian Journal of Pharmaceutical Research and Development, 2024)
This review provides a comprehensive analysis of solid lipid nanoparticles (SLNs) as promising drug delivery systems. SLNs have garnered significant attention due to their unique properties, including biocompatibility, controlled drug release, and improved stability. The abstract explores the key aspects of SLN formulation, emphasizing the influence of lipid composition, surfactants, and production methods on particle size, drug loading, and release kinetics. The impact of these parameters on the pharmacokinetics and therapeutic efficacy of SLN-incorporated drugs is discussed. Furthermore, the review delves into the various methods employed for characterizing SLNs, such as dynamic light scattering, transmission electron microscopy, and X-ray diffraction, highlighting their roles in ensuring product quality. The abstract also touches upon recent advancements in SLN research, including surface modification strategies and their implications for targeted drug delivery.In conclusion, this review consolidates current knowledge on SLNs, offering valuable insights into their formulation, characterization, and potential applications in pharmaceutical research. The synthesis of relevant literature provides a foundation for researchers and practitioners to navigate the evolving landscape of SLN-based drug delivery systems.